Optimization of the Fermentation Process for Pine-needle Sweet-potato Glutinous Rice Wine and Analysis of Its Antioxidant Activity - Jie YOU; Rusheng XIE; Weibin WU (Shipin gongye ke-ji)
Objective: In order to improve the flavor and efficacy of traditional sweet-potato glutinous rice wine, optimize the fermentation process of pine-needle sweet-potato glutinous rice wine and evaluate its physicochemical indexes and antioxidant activity. Methods: Based on the traditional fermentation of sweet-potato rice wine, the fermentation conditions were optimized using a single-factor experiment and the response surface method. The effects of pine-needle addition, initial sugar content, fermentation time, yeast addition, solid-liquid ratio, and fermentation temperature on the fermentation process were investigated. The physicochemical indexes of the pine-needle sweet-potato glutinous rice wine obtained under the optimal fermentation conditions were evaluated. In addition, its antioxidant activity was analyzed by 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonate) (ABTS) cation free radical scavenging experiments. Results: The optimized fermentation conditions were as follows: pine needle mass addition of 3.3%, initial sugar content of 22.5°Bx, fermentation time of 7 d, yeast mass addition of 0.20%, solid (raw material mass):liquid (distilled water volume) ratio of 1:3 (g/mL), and fermentation temperature of 30 ℃. Under these conditions, the resulting pine-needle sweet-potato glutinous rice wine had a total sugar content of 12.5 g/L, alcohol content of 17.6%, and amino acid nitrogen content of 0.58 g/L. The resulting product exhibited a light-yellow transparent appearance with a unique pine-needle herb aroma. Moreover, it satisfied physical, chemical, and microbial safety standards. In terms of antioxidant capacity, the scavenging rates of the DPPH and ABTS+ free radicals of the pine-needle sweet-potato glutinous rice wine were as high as 87.2% and 90.3%, respectively, which were significantly higher than those of traditional sweet-potato glutinous rice wine (P<0.05). Conclusion: The optimized fermentation process developed in this study improved the flavor of pine-needle sweet-potato glutinous rice wine and significantly enhanced its antioxidant properties. Therefore, this process has practical application value for promoting the innovation and upgrading of traditional sweet-potato glutinous rice wine and providing new ideas for the application of plant excipients in wine products.